Concomitant Psychiatric and Nonalcohol‐Related Substance Use Disorders Among Hospitalized Patients with Alcoholic Liver Disease in the United States. (1st January 2018) - Jinjuvadia, Raxitkumar; Jinjuvadia, Chetna; Puangsricharoen, Pimpitcha; Chalasani, Naga; Crabb, David W.; Liangpunsakul, Suthat; ,
Abstract : Background: Despite that the epidemiological studies on the comorbidity of alcohol misuse and psychiatric disorders have been studied, less is known about the magnitude of these disorders among patients with alcoholic liver disease (ALD). Our aim was to determine the prevalence of psychiatric and substance use disorders among hospitalized ALD patients in the United States. Methods: We utilized a single‐level clinical classification software to identify patients with ALD and psychiatric/substance use disorders from the 2011 National Inpatient Sample data. The primary outcome was the prevalence of these disorders among hospitalized patients with ALD ( n = 74, 972) compared to those with chronic liver diseases not caused by alcohol ( n = 350, 140) and those without underlying liver diseases ( n = 1, 447, 063). Results: The prevalence of adjustment disorder, anxiety disorder, posttraumatic stress disorder, and depression was significantly higher among hospitalized patients with ALD when compared to those with chronic liver diseases not caused by alcohol (all with p ‐values <0.05). Younger age, female gender, and White race were the independent predictors of psychiatric/substance use disorders among hospitalized patients with ALD. Conclusions: Hospitalized patients with ALD have significantly high prevalence of concomitant psychiatric and substance abuse disorders when compared to those with chronic liver diseases not caused by alcohol and those without underlying liver diseases. Screening and appropriate intervention should be implemented as part of routine clinical care for these patients. Abstract : Less is known about the magnitude of psychiatric disorders among patients with alcoholic liver disease (ALD). Using 2011 National Inpatient Sample data, we found significantly higher prevalence of several psychiatric and substance use disorders among hospitalized patients with ALD when compared to those with chronic liver diseases not caused by alcohol and those without underlying liver diseases. Screening and appropriate intervention for psychiatric disorders should be implemented as part of routine clinical care for these patients.